A scoping review of cost‐effectiveness analyses of school‐based interventions for caries. Issue 5 (16th June 2020) - Amilani, Uttara; Carter, Hannah E.; Senanayake, Sameera; Hettiarachchi, Ruvini M.; McPhail, Steven M.; Kularatna, Sanjeewa
Abstract: Objectives: The aims of this study were to: identify the evidence on cost‐effectiveness of school‐based interventions for caries prevention globally up to 2019; summarize key characteristics of interventions applied within this setting; summarize the reporting quality of previous studies; and to identify and analyse knowledge gaps. Methods: A scoping review of published literature on the cost‐effectiveness of school‐based interventions to prevent child tooth decay was conducted. A search in Medline, Cinahl and Embase was performed with no date restriction. Reporting quality of the included studies was assessed against Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. Results: Of the 738 records identified in the initial search, 15 studies met the pre‐specified inclusion criteria. The majority were published after 2011 (n = 9, ) and applied to high‐income countries (n = 12). Nearly 80% of the studies assessed the cost‐effectiveness of the interventions based on topical fluoride therapies and fissure sealants at school premises. Although, the outcome measures differed across the studies, almost all the caries preventive interventions were cost‐saving or cost‐effective when compared with usual care. Compliance with the CHEERS checklist differed. Conclusions: There is evidence to suggest that school‐based caries preventive interventions are cost‐effective, and in some cases cost‐saving. Further evidence is required from low‐ to middle‐income countries to confirm the generalizability of these findings. Future studies should consider adopting Quality Adjusted Life Years as a generic outcome measure that would enable the cost‐effectiveness findings to be compared across different types of interventions and diseases. Improved standardization and quality of reporting are also required.